Colonial Continuities: Human Rights, Terrorism, and Security Laws in India - Kalhan, Anil; Conroy, Gerald P.; Kaushal, Mamata; Miller, Sam Scott (Columbia Journal of Asian Law, 2006)
In 2004, India took a significant step forward for human rights by repealing the Prevention of Terrorism Act of 2002, which had established a permissive set of legal rules to prosecute acts of terrorism largely outside the ordinary rules of the regular criminal justice system. While POTA itself was enacted in the aftermath of the major terrorist attacks of 2001 in both the United States and India, the statute built upon a long tradition of antiterrorism and other security laws in India dating since well before independence. While India has faced serious threats from terrorism and other forms of politicized violence for decades, these special antiterrorism laws have not proven particularly effective in combating terrorism. Terrorism has persisted as a problem notwithstanding these laws, under which few of the individuals charged have been convicted. Moreover, like antiterrorism laws in other countries, including the United States, aspects of India’s antiterrorism laws have raised significant human rights concerns. Some of those concerns have remained even in the aftermath of POTA’s repeal, since the Indian government has preserved many of the law’s provisions in other statutes. Other, similar laws also remain in place at both the central and state levels, such as the Unlawful Activities (Prevention) Act. Attentiveness to these human rights concerns is not simply a moral and legal imperative, but also a crucial strategic imperative. As the Supreme Court of India has recognized, “[t]errorism often thrives where human rights are violated,” and “[t]he lack of hope for justice provides breeding grounds for terrorism.” Since terrorists often deliberately seek “to provoke an over-reaction” and thereby drive a wedge between government and its citizens – or between ethnic, racial, or religious communities – adhering to human rights obligations when combating terrorism helps to ensure that advocates of violence do not win sympathy from the ranks of those harmed and alienated by the state.